A qualitative exploration of the barriers and facilitators to self‐managing multiple long‐term conditions amongst people experiencing socioeconomic deprivation - Abi Woodward; Danielle Nimmons; Nathan Davies; Kate Walters; Fiona A. Stevenson; Joanne Protheroe; Carolyn A. Chew‐Graham; Megan Armstrong (Wiley, 2024)
Abstract Background Globally, it is estimated that one in three adults live with two or more long‐term conditions (multiple long‐term conditions, MLTCs), that require self‐management. People who experience socioeconomic deprivation face significant health inequalities due to a range of interrelated characteristics that lead to a lack of resources and opportunities. Previous research with underserved populations indicate low levels of trust towards primary care providers and potential barriers for developing patient‐healthcare professional relationships. The purpose of this paper is to explore the barriers and facilitators to self‐managing MLTCs, amongst people who experience socioeconomic deprivation. Methods Semistructured one‐to‐one interviews with adults (n = 28) living in London and Sheffield, United Kingdom with MLTCs who are experiencing socioeconomic deprivation. Participants were recruited through general practices, community channels and social media. Data were analysed in NVivo using reflexive thematic analysis methods. Findings Four analytical themes were developed: (1) challenges in accessing healthcare services, financial assistance, and cultural awareness; (2) empowerment and disempowerment through technology, including digital exclusion, and use of technology; (3) impact and causes of exclusion on self‐management, including social isolation, area‐based and economic exclusion, and health‐related stigma and (4) adapting self‐management strategies, including cost‐effective, and culturally/lifestyle appropriate strategies. Conclusions Future health interventions and services need to be developed with consideration of the combined complexities of managing MLTCs while experiencing socioeconomic deprivation. Increased awareness in practitioners and commissioners of the complexities surrounding the lives of people experiencing socioeconomic deprivation, and the need for targeted strategies to promote self‐management of MLTCs are of great importance. Patient or Public Contribution A patient advisory group contributed to all stages of the study, including providing important feedback on study documents (topic guides and recruitment materials), as well as providing critical insights surrounding the interpretation of interview data.